Improving the reaction capacity of EGB students in the eighth year - Mario Alberto Cabezas Guerrero, Jimmy Manuel Zambrano Acosta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The training of physical abilities allows coordinative abilities such as balance, agility, coordination and reaction capacity together with other physical abilities to be considered as the basis for a person to develop locomotion activities optimally, in special for adolescents to carry out exercises for the development of their capacities as biopsychosocial being, the central objective of the research was oriented in the elaboration of an exercise program for the improvement of the reaction capacity in the students of eighth year of general education basic, for this I apply an explanatory level methodology, of a quantitative, quasi-experimental retrospective longitudinal nature, since the 2019 - 2020 school year was analyzed, due to the fact that evaluations were carried out on the sample through the application of the initial test and In the end, empirical, theoretical, analytical research methods were used. lysis, synthesis, induction and deduction to arrive at the answer to the question: What is the incidence of the exercise program to improve the reaction capacity in the eighth year students of higher basic education of the San Camilo educational unit? concluding that, according to the records of the times in the execution of the test, both initial and final, it was evidenced that the plyometric exercises developed in the proposed exercise program served to improve the reaction capacity of the eighth-year students. EGB of the educational unit San Camilo